Toged Gugat Penari Tayub dalam dialetik Feminisme - SUKARNO Santoso
Joged creation of theatrical performance inspired by the story of Sue the Ledhek Blora that not only highlight the dancing abilities , but also must mentally prepare spiritualy for their work as Ledhek.A ledhek must continue to hone their know ledge in order not to lose by ledhek-ledhek others.Though they still have to maintain the household ,serving her husband and raising children. The process of creation of this work is based on the theory of realisme and feminisme.Realism is the flowor the doctrine that always hold on reality . Realism trying to express the reality of the issue in accordance with the fact that there is and always aims to present art in order to bring the other goals behind it. Realism is understood as the universe of thingking that brings insinght and perception .the concept of Realism stage play requires a cript is good ,also the visual aspect of the stage which includes blocking ,lighting ,and acting are arranged neatly. thus , realism is confronts an oral cultrue with the culture of writing , improvisation culture with a cultures .Realism aims to create the illusion of reality that is manifested in the form of staging by describing the human life situation objectively without any process of distortion in it.